Lesbian, Gay, Bisexual, Transgender, Intersex, and Queer Concerns in Professional Psychology Education - Collens, Paula; Du Preez, Elizabeth (University of Waikato, 2023)
Best practice guidelines for psychologists working with lesbian, gay, bisexual, transgender, intersex, and queer+ (LGBTIQ+) people and position statements against “conversion therapies” have been published internationally. These call for professional psychologist education to develop competence for work with this community, but studies show variability and lack of inclusion of LGBTIQ+ content in professional programmes in higher education institutions. A critical narrative review examined approaches to the inclusion of LGBTIQ+ concerns in the education of psychologists. A systematic literature search identified 33 papers for review. Synthesis of findings highlighted benefits and challenges of the cultural competence approach to LGBTQ+ curricular inclusion; a contested pedagogic space relating to religious belief, homophobia, and sexualities; a shift in psychology to include resilience-based frameworks of sexuality and gender diversity; and finally disaggregation of the LGBTQ+ umbrella with emergence of transgender and gender diversity focused research. Lack of research relating to people with intersex variations and the need for LGBTIQ+ representation/voices in this research area were evidenced.
Keywords: 13 Education; 39 Education